Management of Traumatic Joint Dislocations in Irrua - Edomwonyi, Edwin Omon; Nwokike, Osita Chizoba; Onuminya, John Enekele (Scientific Research, 2015)
Aim: To elucidate the pattern of presentation and management of traumatic major joint dislocations as seen in Irrua Specialist Teaching Hospital. Method: A five-year retrospective review of 44 cases in 43 patients. Data were retrieved from the Medical Records Department of the hospital. Results: Forty-four cases of traumatic dislocations were reviewed in 43 patients. Male to female ratio was 7.6:1. Median age was 33 years. The majority of patients were in the 3rd decade of life. Patients below 40 years accounted for 62.79% of cases. Twenty-four (55.81%) patients had hip dislocation. Knee dislocations were the least, accounting for 2.32% of cases. All cases except three resulted from road traffic accidents (RTAs). None had neurologic deficits. Nineteen (44.23%) patients had isolated injuries. 76.7% cases presented in less than 6 hours. All shoulder dislocations were anterior while all elbow dislocations were posterior. All except 3 cases were managed by closed manipulation under general anaesthesia. Two patients died from associated head injury. Fourteen patients discharged against medical advice while recuperating in the ward. Follow-up was however difficult as a significant number did not turn up. Conclusion: Hip dislocation is the commonest variety of traumatic dislocation in our setting. A majority of cases were amenable to closed manipulation and immobilization. Road traffic accidents accounted for the majority.
Keywords: Presentation Pattern; Trauma; Joint Dislocation; Treatment; Effect